A Usual G‐Protein‐Coupled Receptor in Unusual Membranes. (3rd December 2015) - Chawla, Udeep; Jiang, Yunjiang; Zheng, Wan; Kuang, Liangju; Perera, Suchithranga M. D. C.; Pitman, Michael C.; Brown, Michael F.; Liang, Hongjun
Abstract: G‐protein‐coupled receptors (GPCRs) are the largest family of membrane‐bound receptors and constitute about 50 % of all known drug targets. They offer great potential for membrane protein nanotechnologies. We report here a charge‐interaction‐directed reconstitution mechanism that induces spontaneous insertion of bovine rhodopsin, the eukaryotic GPCR, into both lipid‐ and polymer‐based artificial membranes. We reveal a new allosteric mode of rhodopsin activation incurred by the non‐biological membranes: the cationic membrane drives a transition from the inactive MI to the activated MII state in the absence of high [H + ] or negative spontaneous curvature. We attribute this activation to the attractive charge interaction between the membrane surface and the deprotonated Glu134 residue of the rhodopsin‐conserved ERY sequence motif that helps break the cytoplasmic "ionic lock". This study unveils a novel design concept of non‐biological membranes to reconstitute and harness GPCR functions in synthetic systems.